Animal Metaphors in English and Kurdish - Dilovan Sayfuddin Saady (Zanco Journal of Humanity Sciences)
This study entitled "Animal Metaphors in English and Kurdish" focuses on animal metaphors .The researcher ,here, brings a number of definitions of the word metaphor . The foremost objective of this research is to know the culture of the two societies as far as the understanding of different types of animals is concerned. The aim is to show what similarities and differences represent cultural connotations in both languages. The significance of the research lies in the fact that learners will be able to comprehend and give the translation of those sentences that contain animal metaphors. It is also important for those who have willingness in understanding the cultures of two different societies as far as animals are concerned. Kurdish students face some problems and difficulties in learning metaphors especially animal metaphors. So, this research could be of a great help for this purpose. The study makes a comparison between English and Kurdish languages as concerned with animal metaphors. Examples from both languages are given to reach the aim .The conclusion of the research shows that there is cultural correspondence between the two languages concerning some animals despite some differences .At the end ,the researcher shows a list of references that are benefited in writing this research.